International Feminist Movements and the Islamic Family Structure: An Analytical Study in the Light of the Prophetic Seerah ﷺ: حقوقِ نسواں کی بین الاقوامی تحریکیں اور اسلامی خاندانی ساخت: سیرتِ محمدی ﷺ کی روشنی میں جائزہ - Zaib, Kalsoom Alam; Ahmed, Dr. Sajjad (Al-Aijaz Research Journal of Islamic Studies & Humanities, 2025)
This article provides an overview of the feminist movement, covering its origins, motivations, theories, and impact. It also examines women’s rights organizations at the international and national levels and their role in shaping modern discourse on women’s rights, particularly how these movements influence Islamic family values. The article analyzes the impact of the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) on the family system, particularly in the context of Islamic law. It explores the historical evolution of family structures, the essential components of a stable family. It presents a critical review of the CEDAW treaty. It explores its historical background, objectives, and objections raised by Muslim countries and Islamic scholars. The study further provides a comparative analysis of CEDAW from the perspective of Islamic jurisprudence, highlighting the conflicting areas between international conventions and Islamic family law. This research adopts an analytical and research-based approach, offering a critical and investigative review of the CEDAW treaty by assessing how its provisions impact the Islamic family system. The study aims to highlight the challenges faced by Muslim societies in balancing modern feminist narratives with Islamic principles while proposing a solution-oriented framework that safeguards both family integrity and women’s legitimate rights.